The Impact of Using Specialist Geotechnical Software in Modeling of Pile Raft Foundation (PRF) - SHOKR, MOHAMED (2019)
Due to rapid urbanization, the construction of tall towers has become common in all the metro cities. The column loads from the towers will be very high depending on the height of the tower and they require very efficient foundation system to carry them. It is very common these days that most of the towers are founded on Piled raft foundation systems. Reinforced concrete slabs of uniform thickness acting as shallow foundations, covering complete plinth area of building are called as Raft foundations. Raft foundations help in distributing the loads from the wall or columns to the lower soil layers effectively. Piled Raft foundation (PRF) is formed by addition of piles to a Raft Foundation and it increases the load bearing capacity. Horizontal loads can be resisted to a maximum extent due to the addition of piles to a raft foundation. Reduction of settlements, both maximum and differential and enhancing the ultimate load capacity will improve the performance of the foundation to a greater extent. Various software’s are available to analyze the piled raft foundations under various loading conditions, for providing the optimum design. Piled raft foundations are analyzed using CSI SAFE by most of the structural engineers. Since the Raft Foundations will be supported directly on soil, structural software like CSI SAFE do not simulate the exact site conditions, since they model the soil only as springs. Hence a sophisticated geotechnical software PLAXIS 3D is used to analyze the results of Piled raft foundation for a case study and the results are compared with the results from the other software. Plaxis 3D have got various constitutive models to simulate the exact ground conditions and simulates the soil structure interaction between the raft, piles and soil more effectively. A case study of one of the towers in Abu Dhabi is considered to check the comparison between two software initially. Later, a typical piled raft foundation is considered based on the typical details of first case study. This dissertation includes the detailed procedure regarding modelling the piled raft for the second case study using both the software, comparison of results and discusses the advantages and disadvantages of both the software in case of geotechnical applications.